The Perceived Social Burden in Celiac Disease - Ciacci, Carolina (Diseases, 2015)
In the present paper, we discuss the change in celiac disease (CD) awareness and perception through patients’ concerns and the most recent literature. Nowadays CD has moved in the public awareness (both doctors and population) from a rare disease to a common one and the gluten free diet (GFD) is no longer the exclusive therapy for CD patients but is becoming a popular health choice for everybody. Gluten-free food, once hard to find and requiring home preparation, is now available at restaurants and grocery stores. However, the quality of life of those affected by CD seems to be still compromised and this is particularly true for those who find it difficult to adhere to a GFD and those who were asymptomatic at the time of diagnosis. Intervention at diagnosis and follow-up to improve the patients’ adaptation to the condition and its limitations should be implemented.